Rate of convergence of Fourier series on the classes of $\overline{ψ}$-integrals - Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We introduce the notion of $\overline{ψ}$-integrals of 2π-periodic summable functions f, f ε L, on the basis of which the space L is decomposed into subsets (classes) $L^{\overline{ψ}}$. We obtain integral representations of deviations of the trigonometric polynomials $U_{n(f;x;Λ)}$ generated by a given Λ-method for summing the Fourier series of functions $f ε L^{\overline{ψ}}$. On the basis of these representations, the rate of convergence of the Fourier series is studied for functions belonging to the sets $L^{\overline{ψ}}$ in uniform and integral metrics. Within the framework of this approach, we find, in particular, asymptotic equalities for upper bounds of deviations of the Fourier sums on the sets $L^{\overline{ψ}}$, which give solutions of the Kolmogorov-Nikol'skii problem. We also obtain an analog of the well-known Lebesgue inequality.